VOCABULARY MASTERY STRATEGIES USED BY INDONESIAN EXTENSIVE READING LEARNERS - Onie Pradina; Listyani Listyani (Universitas Muria Kudus, 2021)
Vocabulary mastery is a key aspect of foreign language leaning. Various methods can be used to improve vocabulary mastery. This present study was conducted to find out what strategies the learners of the Extensive Reading Course used in mastering the vocabulary in an English Language Education Program (ELEP) at a private university in Central Java, Indonesia, based on the Schmitt (2000) theory. The strategies discussed in this study are the determination, metacognitive, cognitive, memory and social strategy. In this study, a qualitative research design was applied to collect the data using questionnaire with open-ended questions. There were fifty-six participants of three Extensive Reading classes for this study. The result of the study showed that the determination strategy was the most preferable. Most of the participants used that strategy to enrich their vocabulary, while the social strategy was the least used. It was found that most of ER learners used determination strategies to mastery vocabulary.